Digitalizing Fatwas: A Jurisprudential Analysis of Muslim Social Interactions in Virtual Spaces - Soviatul Awaliah; Fati Rahma Rahim; Muhammad Husain (Al-Qalam Institute, 2025)
This research aims to examine the application of fiqh in online Muslim communities and to identify how social interaction and religious practices in digital spaces are regulated within the framework of Islamic law. This research focuses on the rapid growth of the Muslim community online, raising challenges for the legitimacy of worship and communication ethics. This study uses a qualitative case study design integrating netnography, in-depth interviews, and document analysis to collect data from digital platforms such as WhatsApp, YouTube, Instagram, and TikTok. The main findings of this study are, first, the deconcentration of religious authorities through digital algorithms that form virtual fatwas; Second, the recontextualization of manners and muamalah that change social ethics from oral communication to digital; and third, rituals that are increasingly fluid in cyberspace, prioritizing the alignment of intentions over physical proximity. The contribution of this research is to provide a contemporary framework of fiqh relevant to the Muslim community in the digital space, as well as recommendations to improve digital literacy among religious institutions. This research proposes that religious authorities understand the role of technology in shaping virtual religious practices.